2018
DOI: 10.3390/w10080972
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Function and Hydrochemistry within a Stratified Anchialine Sinkhole: A Window into Coastal Aquifer Interactions

Abstract: Anchialine sinkholes provide insight into coastal aquifer systems and coastal mixing processes. Aquifer microbial community function is usually inferred from hydrochemical information, but there are few direct studies of microbial communities in the Floridan Aquifer. Hospital Hole is a 43 m-deep stratified sinkhole under the Weeki Wachee River, FL, with three distinct brackish layers: a hypoxic layer, a chemocline and a sulfidic anoxic layer. Illumina sequencing and bioinformatic tools were used to reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 29 publications
(51 reference statements)
4
36
0
Order By: Relevance
“…The presence of soil and enteric bacteria identified in Monte Conca are consistent with other subsurface studies [e.g. 41,42,46,50]. Molecular-grade water processed through each step in the biological analyses process did not yielded these genera, therefore it is unlikely that these communities are the result of process contamination.…”
Section: Plos Onesupporting
confidence: 86%
“…The presence of soil and enteric bacteria identified in Monte Conca are consistent with other subsurface studies [e.g. 41,42,46,50]. Molecular-grade water processed through each step in the biological analyses process did not yielded these genera, therefore it is unlikely that these communities are the result of process contamination.…”
Section: Plos Onesupporting
confidence: 86%
“…The microbial diversity, abundance and activity in such environments become a popular topic of research. Extensive studies on the microbial diversity and abundance in anchialine caves began to emerge in recent years (Seymour et al, 2007; Garman et al, 2011; Krstulović et al, 2013; Davis and Garey, 2018). Based on the 16S rRNA gene, many species in the Jewfish Sink were found to be similar to those in other anoxic environments, and the microbial community in the sink was rich in species likely to be involved in the sulfur, nitrogen and methane cycles (Garman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Krstulović et al (2013) studied the bacterial abundance and diversity in two anchialine caves (Bjejajka Cave and Lenga Pit) located on Mljet Island and found that the microbes in both caves exhibited lower diversity, higher abundances and unique compositions, with Epsilonproteobacteria representing the most abundant group. In the Hospital Hole, there are unique microbial communities in each layer, and sulfur oxidation and nitrogen reduction, which are often coupled, were the predominant ecological functions (Davis and Garey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research findings demonstrated the inverse Pearson relationship of Vibrio with dissolved oxygen, pH and nutrient availability (Prasanthan et al 2011). The bacteria Hypnocyclicus was identified from river water (hospital hole) where sulphide and nitrate reduction reported to be linked with the increased abundance of this bacteria (Davis and Garey 2018). Haliscomonobacter was characterized from the aeration tanks of sewage and waste water treatment plants from paper industry and also reported to play a positive role in water remediation (Fourest et al 2004).…”
Section: Correlation Between Bacterial Abundance and Aquaculture Watementioning
confidence: 99%